Enhancement of Fibrinolysis by Venous Occlusion Results of Long-Term Thrombelastography and Activator Determination - Holzknecht, F; Spöttl, F; Braunsteiner, H (Thrombosis and Haemostasis, 1969)
Global fibrinolysis and activator activity were investigated in venous blood before and after occlusion. Global fibrinolysis was determinated by thrombelastography with a low speed of the paper drive (longterm thrombelastography). The fibrinolysis on the thrombelastographic curves were evaluated by the slant (a°) of the inflectional tangent at the thrombelastographic branch.A considerable increase of global fibrinolytic activity and also of the activator activity after venous congestion was found. There was a slight correlation between the global fibrinolysis and the activator before occlusion and a strong correlation after congestion. There was, however, no accordance between the regression lines of the two correlations. Other factors of activation of fibrinolysis may be involved.